Design of Channel Estimation and Channel Equalization Scheme for Massive MIMO-OFDM Communication System - Sun, Jing; Md Johar, Md Gapar; Tham, Jacquline (International Journal of Computer Science and Information Technology, 2025)
The combination of massive MIMO (massive multiple input multiple output) technology and OFDM (orthogonal frequency division multiplexing) technology has become one of the key technologies in modern wireless communication systems. With the increase in the number of antennas and the complexity of communication channels, channel estimation and channel equalization have become important technical means to ensure system performance. In this paper, a channel estimation method and an adaptive equalization method based on the guide frequency signal are proposed to address the problems of channel distortion and inter-symbol interference (ISI) in massive MIMO-OFDM systems by designing an efficient channel estimation and equalization strategy in order to improve the system performance. In this paper, we first establish the channel model, design the system frame diagram, and analyze the data processing flow, then compare several channel estimation and equalization methods, propose a channel estimation method based on the guide signal, and select an adaptive equalization method for performance optimization. The proposed scheme has a large potential value in reducing the bit error rate (BER), improving the system capacity and anti-interference capability.